2017
DOI: 10.1111/1756-185x.13243
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of the persistence on bDMARDs prescribed for the treatment of rheumatoid arthritis in the Australian population

Abstract: Treatment persistence was longer on tocilizumab followed by abatacept then SC-anti-TNF therapy and was influenced by co-therapy. Glucocorticoid dosage decreased with bDMARD use. This real-world data highlights that persistence on bDMARDs differs according to biologics mode of action and co-therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
4
14
1
Order By: Relevance
“…Studies on data from other registers, focusing on treatment with bDMARDs other than abatacept reported better response and survival on drug in bionaïve patients as compared with bDMARD experienced patients [27][28][29][30][31]. Several studies described the same pattern for abatacepttreated patients [32][33][34], which is in line with our finding, although we suggest that this may partly be due to confounding by other factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies on data from other registers, focusing on treatment with bDMARDs other than abatacept reported better response and survival on drug in bionaïve patients as compared with bDMARD experienced patients [27][28][29][30][31]. Several studies described the same pattern for abatacepttreated patients [32][33][34], which is in line with our finding, although we suggest that this may partly be due to confounding by other factors.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, sex did not predict HAQ response in the present study. Our data on the benefit of methotrexate are in line with those from an Australian retrospective cohort [33] and the ACTION study, where association of methotrexate with a longer survival on abatacept was also demonstrated in patients previously exposed to bDMARDs [34]. The predictive value of pain for survival on abatacept was reported in the ACTION study too, with results going in the same direction as in our study [34].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, patients in the present analysis with any change in corticosteroid dose had an overall reduction in daily dose from baseline to month 6 [mean (SD) change,  − 2.2 (9.0) mg]. Corticosteroid-sparing effects of TCZ have similarly been observed in other real-world studies of TCZ use in routine practice conducted in Japan [9], France [25, 26], Australia [27], Germany [28], and the USA [29]. Together, these findings show that both TCZ monotherapy and combination therapy reduce the need for corticosteroids in patients with RA.…”
Section: Discussionsupporting
confidence: 65%
“…Several observational studies and biologic registries have contributed to a wealth of available data regarding the long-term efficacy and safety of these agents [18, 19, 21, 23, 25]. Furthermore, observational studies have highlighted the importance of real-world persistence, defined as the time from the index dose to the time of switching to a different biologic or the time of the last dose/censoring, as a surrogate for treatment effectiveness and a factor to consider when choosing between agents [20, 28]. These studies showed that first-line abatacept treatment had higher persistence rates than TNFis [20, 28].…”
Section: Discussionmentioning
confidence: 99%